Proceedings of Eurosensors 2017, Paris, France, 3–6 September 2017 2017
DOI: 10.3390/proceedings1040343
|View full text |Cite
|
Sign up to set email alerts
|

MEMS Inertial Switch for Military Applications

Abstract: We developed a MEMS inertial switch (hereafter, the switch) for an ignition system of missiles. The developed switch consists of four folded beams and a plate suspended by the beams, analogous to a well-known spring-mass system. The plate and four beams compose a single body, which is made from single crystalline silicon wafers by deep reactive ion etching techniques. This process gives high thermal stability and stress-free structure. The switching, either open or close a conductive path, is achieved by the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…On the other, low-g inertial switches, widely used in the aviation and automotive industries, have acceleration responses ranging from several milli g to hundreds of g. Based on a feasibility study, Lior et al [84] proposed an idea of using a pair of bistable beams to suspend the proof mass and to sense the acceleration, in which the switch can be closed under sub-g inertias. Nam Lee et al [85] have developed an inertial switch with a threshold acceleration of no more than 10 g, and it can withstand unexpected shocks of up to 1000 g, making it suitable for harsh military environments. Rigid electrodes of MEMS switches have the problems of short contact time and signal bounce.…”
Section: Passive Inertial Switchesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other, low-g inertial switches, widely used in the aviation and automotive industries, have acceleration responses ranging from several milli g to hundreds of g. Based on a feasibility study, Lior et al [84] proposed an idea of using a pair of bistable beams to suspend the proof mass and to sense the acceleration, in which the switch can be closed under sub-g inertias. Nam Lee et al [85] have developed an inertial switch with a threshold acceleration of no more than 10 g, and it can withstand unexpected shocks of up to 1000 g, making it suitable for harsh military environments. Rigid electrodes of MEMS switches have the problems of short contact time and signal bounce.…”
Section: Passive Inertial Switchesmentioning
confidence: 99%
“…Based on a feasibility study, Lior et al [ 84 ] proposed an idea of using a pair of bistable beams to suspend the proof mass and to sense the acceleration, in which the switch can be closed under sub- g inertias. Nam Lee et al [ 85 ] have developed an inertial switch with a threshold acceleration of no more than 10 g , and it can withstand unexpected shocks of up to 1000 g , making it suitable for harsh military environments.…”
Section: Classification Of Mems Switches Based On Driving Principlmentioning
confidence: 99%
“…The inertial switch is turned on when the missile is subjected to an acceleration at or above a predetermined threshold level. Lee et al [25] reported a MEMS switch that is applicable to the safe-and-arm device of a rocket motor ignition system for cold launched missiles. The main goal of the work is to realize a MEMS inertial switch, which can be triggered at a low-g level (about 10g) in the sensitive direction.…”
Section: Military Applicationmentioning
confidence: 99%
“…Therefore, micromachined inertial switches are designed for variety of different threshold levels, which can be applied to various applications. We can classify two main categories according to the threshold levels [23][24][25][26]: the relatively high-g (i.e. 100 g, 1000 g) switch and the low-g switch (i.e.…”
Section: Key Performance Parameters Of Micromachined Inertial Switchesmentioning
confidence: 99%
“…The inertial impact switch is widely used as the priming control unit in fuze field. In the electromechanical trigger fuze, the inertia switch is used to control the working state of the first generation explosive element while it is used for the fuse proximity failure and landing backup firing in the shell radio fuze [1][2][3]. Due to the complex heat treatment process of materials, spring wire diameter , structural design as well as the adverse ballistic environment, most switches failure within the threshold range [4].…”
Section: Introductionmentioning
confidence: 99%